"Can Catholicism Validate Jewish Biblical Interpretation?" -- A Reply to Jon D. Levenson - Wansbrough, OSB, Henry (Studies in Christian-Jewish Relations, 2011)
This article is a response to the article by Jon Levenson in volume 1 of Studies in Christian-Jewish Relations, which asked the question, "Can Catholicism Validate Jewish Biblical Interpretation?" The author, a member of the Pontifical Biblical Commission during its work on the study, The Jewish People and Their Sacred Scriptures in the Christian Bible, engages some of Levenson's reservations about that work. Among the topics discussed are the authority of the study, the perils of religious relativism, and Paul's understanding of the Law in reference to Christ.